139k views
5 votes
(2x + y)2 – (3x – 2y)2 + (x – 4y)(x + 4y
11​

User Dinah
by
5.3k points

1 Answer

4 votes

Answer:

Explanation:

(a+ b)² = a² + b² + 2ab

(2x + y)² = (2x)² + y² + 2*2x *y

= 4x² + y² + 4xy

(a- b)² = a² + b² - 2ab

(3x - 2y)² = (3x)² + (2y)² - 2*3x *2y

= 9x² + 4y² - 12xy

(a - b)(a +b) = a² - b²

(x - 4y(x + 4y) = x² - (4y)²

= x² - 16y²

(2x + y)² - (3x - 2y)² + (x - 4y)(x +4y)

= 4x² + y² + 4xy - (9x² + 4y² - 12xy) + x² - 16y²

= 4x² + y² + 4xy - 9x² - 4y² + 12xy + x² - 16y²

= 4x² - 9x² + x² + y² - 4y² - 16y²+ 4xy + 12xy

= -4x² - 19y² + 16xy

User Waheed
by
6.0k points